Chemical composition of Oil Palm Frond (OPF) at different age - Mat Rewai, Ahmad Aizat; Abdullah, Azuandi; Abdul Razak, Mohd Muhaimim; Yahaya, Muhammad Syafiq (2012)
This project is a study about chemical components of oil palm frond (Elaeis quineensis). Oil palm is the most important agricultural crop of Malaysia. Agricultural oil palm produce many waste material from that tree such as oil palm frond (OPF), oil palm trunks (OPT) , empty fruit brunch (EFB) , palm kernel shell (PKS) and others. There are seven experiments have done in this study namely determination of moisture content, cold water solubility, hot water solubility, alcohol-benzene solubility, 1% NaOH solubility of wood, lignin content and ash content in wood. The percentage of result shows the content of chemical component in wood such as extractive components, lignin and ash.